Comparing nadir and limb observations of polar mesospheric clouds: The effect of the assumed particle size distribution. (May 2015) - Bailey, Scott M.; Thomas, Gary E.; Hervig, Mark E.; Lumpe, Jerry D.; Randall, Cora E.; Carstens, Justin N.; Thurairajah, Brentha; Rusch, David W.; Russell, James M.; Gordley, Larry L.
Abstract: Nadir viewing observations of Polar Mesospheric Clouds (PMCs) from the Cloud Imaging and Particle Size (CIPS) instrument on the Aeronomy of Ice in the Mesosphere (AIM) spacecraft are compared to Common Volume (CV), limb-viewing observations by the Solar Occultation For Ice Experiment (SOFIE) also on AIM. CIPS makes multiple observations of PMC-scattered UV sunlight from a given location at a variety of geometries and uses the variation of the radiance with scattering angle to determine a cloud albedo, particle size distribution, and Ice Water Content (IWC). SOFIE uses IR solar occultation in 16 channels (0.3–5 μm) to obtain altitude profiles of ice properties including the particle size distribution and IWC in addition to temperature, water vapor abundance, and other environmental parameters. CIPS and SOFIE made CV observations from 2007 to 2009. In order to compare the CV observations from the two instruments, SOFIE observations are used to predict the mean PMC properties observed by CIPS. Initial agreement is poor with SOFIE predicting particle size distributions with systematically smaller mean radii and a factor of two more albedo and IWC than observed by CIPS. We show that significantly improved agreement is obtained if the PMC ice is assumed to contain 0.5% meteoric smoke by mass, in agreement with previous studies. We show that the comparison is further improved if an adjustment is made in the CIPS data processing regarding the removal of Rayleigh scattered sunlight below the clouds. This change has an effect on the CV PMC, but is negligible for most of the observed clouds outside the CV. Finally, we examine the role of the assumed shape of the ice particle size distribution. Both experiments nominally assume the shape is Gaussian with a width parameter roughly half of the mean radius. We analyze modeled ice particle distributions and show that, for the column integrated ice distribution, Log-normal and Exponential distributions better represent the range of masses that contribute to the IWC. We further show that agreement between SOFIE and CIPS is further improved with the assumption of either Log-normal or Exponential ice particle size distributions. This improvement suggests that the range of mass bearing particle radii is larger, but not significantly shifted from what is obtained by assuming a Gaussian distribution. The assumption of an Exponential particle size distribution, as shown to be justifiable here, has the attractive benefits of being characterized with a single parameter, the mean radius, which greatly facilitates studies of the spatial and temporal variation of PMC particle size distributions as well as comparisons between observations and models. Overall, our results represent a validation of both the CIPS and SOFIE datasets. Highlights: SOFIE observations are used to predict the mean PMC properties observed by CIPS. Agreement is obtained if PMC ice is assumed 0.5% meteoric smoke by mass. Better agreement assuming Log-normal or Exponential particle size distributions. The range of mass bearing particle radii is larger than previously assumed. Overall, our results represent a validation of both the CIPS and SOFIE datasets.